Whitney Block Estimation for Flexural Strength of UHPC Beams ‎ (Journal of University of Babylon for Engineering Sciences, 2022)
Despite the development of modern building materials, including Ultra High Performance Concrete (UHPC) and the development of their resistance, the calculations of the flexural strength of structural members remained somewhat complicated and far adequate accuracy. The aim of this study is to present a simple accurate practical model for calculating the flexural strength by using compressive and tensile equivalent stresses with strain compatibility inclusion. Compressive equivalent stress was derived in a manner similar to Whitney Block in normal concrete by converting trapezoidal stress distribution into rectangular stress and providing an equation for both ratios of equivalent height to neutral axis (β) and the ratio of rectangular and trapezoidal stress intensity (k3). The tensile stress was also modeled as equivalent block. Nine UHPC beams were fabricated and casted to study three main variables, which are compressive strength, ratio of longitudinal steel bars and volumetric fraction of steel fibers. The present flexural strength equation gave very similar results to the experimental.